Recent progress on the mechanical exfoliation of 2D transition metal dichalcogenides - Yangang Li; Guizhi Kuang; Zhongjie Jiao; Lin Yao; Ruihuan Duan (Materials Research Express, 2022)
Two-dimensional (2D) transition metal dichalcogenides (TMDs) have attracted extensive attraction due to their unique properties in novel physical phenomena, such as superconductors, Moiré superlattices, ferromagnetics, Weyl semimetals, which all require the high quality of 2D TMDs. Mechanical exfoliation (ME) as a top-down strategy shows great potential to obtain 2D TMDs with high quality and large scale. This paper reviews the theoretical and experimental details of this method. Subsequently, diverse modified ME methods are introduced. Significantly, the recent progress of the Au-assisted ME method is the highlight. Finally, this review will have an insight into their advantages and limitations, and point out a rational direction for the exfoliation of TMDs with high quality and large size.